Money supply growth and unemployment rate in Nigeria: Investigating a long-run relationship using asymmetric ARDL approach - Kufre J. Bassey (West African Journal of Monetary and Economic Integration, 2017)
This paper examines the role of money supply in determining unemployment rate in Nigeria. We employ a nonlinear autoregressive distributed lag (NARDL) model to examine the pass-through effect of the growth in money supply into unemployment rate using time series data over the period 1985 - 2015. Our approach allows for simultaneous test of the short- and long-run nonlinearities characterizing many macroeconomic variables through positive and negative partial sum decompositions of the money supply growth. We obtain the asymmetric dynamic multiplier that graphically depicts the traverse between the short- and the long-run responses of unemployment rates to the positive and negative money supply growth shocks. Our result suggests that money supply plays an important role and reveal that there is a significant pass- through effect of the money supply growth to unemployment rate in the long run. This finding infers that imposing a long- run symmetry where the underlying relationship is actually nonlinear will confound efforts to test for the existence of a stable long-run relationship between unemployment and money supply growth in Nigeria, and hence results in spurious dynamic responses. It also underscores the importance of correctly capturing short-run symmetries (asymmetries) in order to illuminate potentially important differences in the response of policy makers to positive and negative shocks.
Keywords: E24; E51; E52; 330; Nonlinear ARDL; Monetary Policy; Money supply; Unemployment